Assessing The Effectiveness Of Nuclear Security Training And Education In Ghana - Michael Nii Sanka Ansah; Boris Stepanov Pavlovich; Paul Atta Amoah; David Okoh Kpeglo; Simon Adu; Bright Kwame Afornu (International Journal of Nuclear Security, 2023)
Growing attention is being given to nuclear power across several African countries, including in Ghana. The world is depending on nuclear energy as a reliable and efficient means of energy generation. Ghana as a country is developing nuclear energy; thus, equal attention must be directed toward nuclear safety and security. Ghana is gradually developing interest in and is devoting substantial required resources to educating and training on nuclear security to meet the standards required by international bodies. Institutions such as the Nuclear Safety and Security Centre and the School of Nuclear and Allied Sciences of the Ghana Atomic Energy Commission are responding to the growing demands of imparting training and education in nuclear and radiation security. Ghana’s attention to nuclear security training and education has led to the development of programs from international agencies, and this development is making significant contributions toward nuclear security in the African region. This paper presents a well-structured curriculum model for a master’s program in nuclear security and makes possible recommendations to effectively train persons in the nuclear-related fields of the country of Ghana. Prospects of employment at stakeholder facilities in Ghana are carefully assessed in the research.
Keywords: nuclear energy; nuclear security; education; course planner; safety